Large-scale atmospheric features favoring the tropical cyclone activity affecting the Guangdong–Hong Kong–Macao Greater Bay Area of China - Chen, Weizhen; Yang, Song; Wu, Zeming; Cai, Fenying (Environmental research letters, 2022)
This study analyzes the large-scale circulation associated with the tropical cyclones (TCs) affecting the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) in southern China during the peak TC season (July–September) from 1980 to 2019. The results show that the frequency of the TCs affecting the GBA is closely tied to a meridional Rossby wave train from Southeast Asia to Northeast Asia, manifested by the important roles of the variability of the monsoon trough (MT) and the western North Pacific subtropical high (WNPSH). In the active GBA TC years, intensified and westward-shifted MT and northeastward-shrunk WNPSH cause anomalous southeasterly wind over the southeast coast of China, and hence more TCs move northwestward to the GBA. Furthermore, the cyclonic convergent conditions related to the tacit-and-mutual configurations of MT and WNPSH favor more TC genesis in the west of 140° E over the WNP via significant larger meridional shear vorticity of the zonal winds, ascending motions, and positive vorticity. Opposite features of wind anomalies and TC genesis are seen in the inactive GBA TC years. Both statistical and numerical analyses confirm that the meridional Rossby wave train is associated with a Matsuno–Gill response to the anomalous convective activity over the western Pacific warm pool, which is maintained by the ascending branches of the La Niña-type Walker circulation over the Pacific and the monsoon-enhanced Walker circulation over the Indian Ocean.